Geotechnical Engineering : Proceedings of the 21st European Young Geotechnical Engineers' Conference Rotterdam 2011 - Barends, F. B. J.; Breedeveld, J.; Brinkgreve, R. B. J., 1965- (IOS Press, 2011)
This book presents the proceedings of the 21st European Young Geotechnical Engineers Conference, held in the Netherlands in September 2011. Six sections cover the topics of: underground construction; pile foundation and ground improvement; soil dynamics; dams, erosion and piping; deformation and soil properties and geothermics. The papers included here present the new and refreshing perspective of young engineers exploring the field of geotechnics. Geotechnical engineering aims to contribute to sustainable living and to the creation of safe, economic and pleasant spaces to live, work and relax.